Impact of tourist and recreational activities on the indicators of soil-ecological monitoring of the adjacent territory of Lake Teletskoe (Altai Mountains) - Olga A. Elchininova (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The increasing recreational load on the ecosystems of the Lake Teletskoe basin, its related obvious damage and the necessity to quantify the ongoing transformations. Aim. To assess the current state of a soil cover of the adjacent territory of Lake Teletskoe in terms of tourism and recreation impact. Methods. Comparative geographical and chemical as well as soil-ecological monitoring of studied indicators of early, short- and long-term diagnostics. Results and conclusions. Because of the tourist activities in the coastal zone of the mountain-forest belt of Lake Teletskoe, a developed path network transforming its natural ecosystems appeared. Some parameters of soil properties and composition on this path and in the sites not affected by recreation differed significantly. The analysis of water extract showed the decrease in acidity, the reduced content of ammonium and nitrate nitrogen, phosphates, a change in the concentration of calcium cations, potassium and magnesium in the top soil layer on the path, as compared to the undisturbed places. Soil trampling by recreants has damaged litter, decreased its thickness or completely destructed the promenade area. Reduction in litter reserves on the moderately developed paths exceeded by more than 2.7–4.0 times, whereas on the well-defined ones (as in the Altai State Biosphere Reserve with the established systemized movement across the territory), litter was absent at all on a few or even single paths. On weakly developed (fresh) paths, litter reserves turned out to be even higher than on the undisturbed areas or on the paths located next to a gravel site. Recreational loads were responsible for the 1.2–1.7 times increase in soil density of the upper (0–5 cm) layer, accompanied by a decrease in soil porosity and air supply. The hardness of soil was 1.3–1.5 times higher on the path than around it. The tourist effect on general physical properties of soil was traced to a depth of 20–30 cm, but maximum changes were noted in its upper (0–5 cm) layer. Recreational loads did not impact essentially on the aggregate soil composition. No significant changes, caused by tourist and recreational activities, were found in the elemental chemical composition of soils. The content of nutrients and lead were within the background and did not exceed the standardized values. The detected high concentrations of arsenic were not associated with the influence of tourist and recreational activities.